2012
DOI: 10.4111/kju.2012.53.6.391
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Clinical Factors for Diagnosis of Incidental Prostate Cancer in the Era of Tissue-Ablative Surgery for Benign Prostatic Hyperplasia: A Korean Multi-Center Review

Abstract: PurposeTo identify potential predictive factors of incidental prostate cancer (IPca) in patients considering tissue-ablation treatment for benign prostatic hyperplasia (BPH).Materials and MethodsFrom the 11 centers, 1,613 men who underwent transurethral resection of the prostate (TURP) or open prostatectomy were included. Before surgery, prostate biopsy was performed in all patients with prostate-specific antigen (PSA) ≥4.0 ng/ml or with abnormal digital rectal examination (DRE) findings. The patients with pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 24 publications
5
28
1
Order By: Relevance
“…However, the rate of incidental prostate cancer in patients with both negative age-specific PSA levels and negative DRE findings was 6.4% (72 of 1127). Yoo and colleagues 3 reported that incidental prostate cancer was found in only 4.8% (78 of 1613) after prostate biopsy in all patients with PSA ≥4.0 ng/mL or with abnormal DRE findings. Meanwhile, despite being performed in the PSA era, our detection rate of incidental prostate cancer on TURP was slightly higher than the other reports (10.1%; 31 of 307); there are 2 possible reasons for this increase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the rate of incidental prostate cancer in patients with both negative age-specific PSA levels and negative DRE findings was 6.4% (72 of 1127). Yoo and colleagues 3 reported that incidental prostate cancer was found in only 4.8% (78 of 1613) after prostate biopsy in all patients with PSA ≥4.0 ng/mL or with abnormal DRE findings. Meanwhile, despite being performed in the PSA era, our detection rate of incidental prostate cancer on TURP was slightly higher than the other reports (10.1%; 31 of 307); there are 2 possible reasons for this increase.…”
Section: Resultsmentioning
confidence: 99%
“…Prostate cancer has been found incidentally in TURP specimens without prior diagnosis in 5% to 13% of patients. [1][2][3] According to the TNM staging system, incidental tumour in less than 5% of resected prostate tissue is subclassified in clinical stage T1a; tumour found in more than 5% of resected tissue is subclassified as T1b. 4 Although most of the incidental prostate cancers are considered clinically insignificant, recent studies have suggested that in some of them, the clinical course becomes more unfavourable.…”
Section: Introductionmentioning
confidence: 99%
“…Prostate hyperplasia is a disease that often occurs in elderly men and is caused by pathophysiological changes after urinary tract obstruction (12). Previous reports have shown that SOL is a safe and efficient treatment for patients with benign prostate hyperplasia after transurethral resection of the prostate (8,13).…”
Section: Discussionmentioning
confidence: 99%
“…13 14 A recent multi-centric review by Yoo et al showed an incidental prostate cancer rate of 4.8% in over 1600 patients. 15 They found that in addition to DRE findings, the combination of transitional zone volume and PSA could be useful predictors of incidental prostate cancer. Overall, these studies continue to support both a decreased overall prevalence of incidental prostate cancer and more specifically pT1b lesions in the modern era.…”
Section: 12mentioning
confidence: 99%
“…Prior to our findings, detection rates in the PSA era ranged from 4.8% to 16.7%. [8][9][10][11][13][14][15] Dellavedova et al found an incidental prostate cancer detection rate of 7% when they reviewed 100 patients who underwent bipolar TURP. 11 Six patients had Gleason grade 3+3 pT1a disease and one patient had Gleason grade 3+4 pT1b disease.…”
Section: 12mentioning
confidence: 99%